Reseña de Deutscher, Guy (2010).Through the Language Glass. Why the World Looks Different in Other Languages - Guijarro Morales, José Luis (Pragmalingüística, 2011)
Se trata de una reseña de Deutscher, Guy (2010).Through the Language Glass. Why the World Looks Different in Other Languages.